The tree that makes water safe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A West German research team has discovered - by accident - a tree in the Sudan whose seeds can render drinking water safe. Moringa oleafera (the horseradish tree) has been used by villagers to remove from their water the mud washed down from the...